2020
DOI: 10.1002/rmv.2160
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered host genetic factors in KSHV infection and KSHV‐related disease development

Abstract: Summary Kaposi's sarcoma‐associated herpesvirus (KSHV) is the etiological agent of Kaposi's sarcoma (KS), the most common AIDS‐related malignancy. It also causes other rare, but certainly underreported, KSHV‐associated pathologies, namely primary effusion lymphoma, multicentric Castleman disease and KSHV inflammatory cytokine syndrome. Epidemiology and pathogenicity studies point to the potential for host genetic predisposition to KSHV infection and/or the subsequent development of KSHV‐associated pathologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 95 publications
(244 reference statements)
0
12
0
Order By: Relevance
“…Chronic exposure of the skin to iron or alumino-silicate might induce localized immune dysfunction which might explain the topography of the lesions at the extremities of the body and its higher incidence in rural regions [77]. Additionally, some association with HLA [80] and other genetic factors with HHV8 infection susceptibility have been also postulated as predisposition factors for KS [81].…”
Section: The Other Forms Of Ks: the Classic Ks And Endemic Ksmentioning
confidence: 99%
“…Chronic exposure of the skin to iron or alumino-silicate might induce localized immune dysfunction which might explain the topography of the lesions at the extremities of the body and its higher incidence in rural regions [77]. Additionally, some association with HLA [80] and other genetic factors with HHV8 infection susceptibility have been also postulated as predisposition factors for KS [81].…”
Section: The Other Forms Of Ks: the Classic Ks And Endemic Ksmentioning
confidence: 99%
“…Thus far, targeted studies or studies of early-onset KS cases have predominantly been used to identify genetic determinants of KSHV susceptibility or KS and MCD development. These studies have identified several interesting candidate polymorphisms, reviewed more extensively Blumenthal et al [ 73 ]. In particular, polymorphism in specific HLA subtypes, in genes involved in regulation of immune responses like NFκB, TRIM31, LY6G6C, and in subtypes of the natural killer cell receptor KIR have been connected to susceptibility to KSHV infection or development of KS or MCD [ 73 ].…”
Section: Why Do Only Some People Develop Kshv-induced Tumors?mentioning
confidence: 99%
“…These studies have identified several interesting candidate polymorphisms, reviewed more extensively Blumenthal et al [ 73 ]. In particular, polymorphism in specific HLA subtypes, in genes involved in regulation of immune responses like NFκB, TRIM31, LY6G6C, and in subtypes of the natural killer cell receptor KIR have been connected to susceptibility to KSHV infection or development of KS or MCD [ 73 ]. A genetic association with both susceptibility to infection and disease development was also found for Ephrin A, a potential entry receptor for KSHV [ 73 , 74 ].…”
Section: Why Do Only Some People Develop Kshv-induced Tumors?mentioning
confidence: 99%
See 1 more Smart Citation
“…An intensive research effort led to important progress regarding KSHV epidemiology, diagnosis, and potential therapeutic and prophylactic strategies ( Gong et al., 2019 ; Holmes et al., 2020 ). The mechanisms involved in KSHV replication, host responses, and pathogenesis have also been extensively studied ( Blumenthal et al., 2020 ; Yu et al., 2020 ; Zhao et al., 2020 ). However, the role of cellular proteins, in particular those present in the endoplasmic reticulum (ER), where viral production occurs, remains only partly characterized.…”
Section: Introductionmentioning
confidence: 99%